(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out phenotypic variability in cultural and biochemical fruit quality traits in peach [Prunus persica (L.) Batsch] and nectarine [Prunus persica (L.) var. nucipersica] during 2017 and 2018. The fruit length, fruit breadth and fruit weight; and fruit quality parameters, viz. flesh firmness, TSS, TA and ripening index were determined. Biochemical fruit quality traits such as ascorbic acid, total phenols, anthocyanins and relative antioxidant capacity were evaluated. Maximum fruit length (50.68 mm), total phenols (30.17 mg/ 100g FW) and relative antioxidant capacity (83.28%) was noted in Flordaglo, whereas, Tropic Beauty recorded maximum fruit breadth (55.17 mm), fruit weight (85.04 g), flesh firmness (14.74 lbf), ripening index (15.92) and ascorbic acid content (5.15 mg/100g FW). Maximum TSS (12.57°Brix) was noted in Florda Grand, while, minimum TA (0.78%) was recorded in Punjab nectarine. Cultivar Punjab Nectarine and Suncoast nectarine have maximum anthocyanin content (10.57 mg/100g FW). The cultivars exhibited wide phenotypic variation in cultural as well as biochemical traits. Such findings would be helpful in the future breeding programs for selecting cultivars having more health enhancing properties and good postharvest efficiency.